2018
DOI: 10.21926/obm.icm.1901010
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Investigation of Neural Changes in Overweight Adults with Food Cravings after Emotional Freedom Techniques

Abstract: Background: This pilot randomised clinical trial investigated the effect of Clinical Emotional Freedom Techniques (EFT) on brain activation in response to food craving stimuli using functional magnetic resonance imaging. EFT is a brief stress reduction technique which involves stating a cognitive statement with stimulation of acupressure points with a tapping technique. Method: Fifteen overweight/obese adults were allocated to a four-week group EFT treatment or control condition and completed a measure of food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
1
29
1
1
Order By: Relevance
“…Penelitian Vural (2019) menyimpulkan bahwa EFT sangat membantu dalam menurunkan kecemasan melahirkan. Penelitian Stapleton et al, (2018) didapatkan hasil EFT dapat menurunkan aktivitas otak daerah limbik dan mengurangi gejala terkait makanan pada individu yang kelebihan berat badan / obesitas. Studi ini juga menjelaskan mekanisme neurologis yang bekerja di balik banyak hasil studi EFT yang berhasil untuk menurunkan berat badan.…”
Section: Pendahuluanunclassified
“…Penelitian Vural (2019) menyimpulkan bahwa EFT sangat membantu dalam menurunkan kecemasan melahirkan. Penelitian Stapleton et al, (2018) didapatkan hasil EFT dapat menurunkan aktivitas otak daerah limbik dan mengurangi gejala terkait makanan pada individu yang kelebihan berat badan / obesitas. Studi ini juga menjelaskan mekanisme neurologis yang bekerja di balik banyak hasil studi EFT yang berhasil untuk menurunkan berat badan.…”
Section: Pendahuluanunclassified
“…Research has also highlighted the neurological mechanisms that underlie successful weight loss through EFT. A pilot RCT investigated the effect of EFT on brain activation in response to food craving using fMRI [46]. Fifteen overweight or obese adults were allocated to a four-week group EFT treatment or control condition.…”
Section: Evidence For Food Cravingsmentioning
confidence: 99%
“…As might be expected from a therapy that includes a strong somatic component, measurable changes in biological markers have been found following EFT treatments. Hormonal shifts have been identified, including reductions in cortisol production that were statistically greater than cortisol reductions following a supportive counselling session [37]. Changes in blood flow patterns within the brain have been identified in pre- and post-treatment fMRI readings [38].…”
Section: The Clinical Eft Protocolmentioning
confidence: 99%
“…Changes in blood flow patterns within the brain have been identified in pre- and post-treatment fMRI readings [38]. Studies examining the epigenetic effects of EFT treatment have found regulation of a range of genes related to health and mental health [37,39,40]. For instance, a one-hour EFT psychotherapy session found that EFT was associated with the regulation of 72 genes, including those involved in learning and memory, regeneration of neural white matter, enhanced synaptic connectivity, neuronal survival after DNA damage, tumor suppression, insulin regulation, heightened immunity, inflammation, and antiviral activity [39].…”
Section: The Clinical Eft Protocolmentioning
confidence: 99%
See 1 more Smart Citation